ASSA14-03-46 Inhibition of late sodium current reduces the reverse rate dependence of action potential duration prolongation induced by L-type calcium channel activator. (1st December 2014) - Wei, X; Wu, L; Huang, S; Yang, Q; Ren, L; Huo, Y
Abstract : Objective: Late sodium current (late I Na ) has been confirmed to contribute to the reverse rate dependence (RRD) of action potential duration (APD) prolongation induced by potassium inhibitor. This study is to determine the role of endogenous late sodium current in the induced RRD of APD prolongation in hearts treated with L-type calcium channel activator Bay K 8644. Methods: New Zealand White rabbit isolated heart preparations were perfused with modified Krebs-Henseleit solution. Hearts were paced at increasing cycle lengths (CLs) of 400, 500, 667, 1000, 1333 and 2000 ms after atrioventricle (AV) block was introduced by themo-ablation of the AV nodal area. Epicardial monophasic action potential duration at 90% completion of an action potential (epi-MAPD90 ) from the left ventricular free wall were recorded and measured. Tetrodotoxin (TTX) at the concentration of 1 µmol/L was used to inhibit late I Na selectively. Results: At CL of 400 ms, epi-MAPD90 was 150.5 ± 2.2 ms (n = 12). When the pacing CL was increased to 500, 667, 1000, 1333 and 2000 ms, the epi-MAPD90 was significantly increased by 10.6 ± 2.9, 27.2 ± 3.0, 39.2 ± 3.8, 48.8 ± 3.5 and 56.6 ± 5.2 ms (n = 12, p < 0.05∼0.001), respectively. Compared with control, 200 nM Bay K 8644 significantly prolonged MAPD90 at all pacing rates (n = 12, P < 0 .01 vs control), and the increase was greater at longer CLs (72.8 ± 6.1 at CL of 2000 ms) than at shorter CLs (16.1 ± 2.4 at CL of 400 ms, p < 0.05). In addition, Bay K 8644 caused polymorphic ventricular tachycardia at longer CLs of 1333 and 2000 ms. In the continued presence of Bay K 8644, TTX significantly reduced the augmentation of RRD of MAPD90 and abolished the ventricular tachycardia. Conclusion: Endogenous late sodium current contributes to the enhanced RRD of APD prolongation induced by L-type calcium channel activator.